2020
DOI: 10.34172/apb.2020.070
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and In Vitro Penetration Study of Recombinant Human Epidermal Growth Factor-Loaded Transfersomal Emulgel

Abstract: Purpose : Recombinant human epidermal growth factor (rhEGF) is a 6045-Da peptide that promotes the cell growth process, and it is also used for cosmetic purposes as an anti-aging compound. However, its penetration into skin is limited by its large molecular size. This study aimed to prepare rhEGF-loaded transfersomal emulgel with enhanced skin penetration compared with that of non-transfersomal rhEGF emulgel. Methods: Three transfersome formulations were prepared with different ratios between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…Also, BBR has low permeability due to the presence of methoxy and ammonium quartener groups in its structure, as shown in Figure 1 (Li et al, 2017;Narade and Pore, 2019). This is in line with a study by Torky et al (2018), which showed that the permeation ability of BBR gel into the skin was restricted and many drugs stayed on the skin surface.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Also, BBR has low permeability due to the presence of methoxy and ammonium quartener groups in its structure, as shown in Figure 1 (Li et al, 2017;Narade and Pore, 2019). This is in line with a study by Torky et al (2018), which showed that the permeation ability of BBR gel into the skin was restricted and many drugs stayed on the skin surface.…”
Section: Introductionsupporting
confidence: 91%
“…The PDI values of the four transfersome formulae were satisfactory. According to Surini et al (2020) and Danaei et al (2018), PDI values less than 0.3 indicated that the particle size distribution of the vesicles is homogeneous and acceptable. Moreover, the PDI of the BBR transfersomes is shown in Table 3.…”
Section: Particle Size Pdi and Zeta Potentialmentioning
confidence: 98%
See 1 more Smart Citation
“…In drug delivery applications using lipid-based carriers, a PDI of 0.3 and below is considered to be acceptable and indicates a homogenous population of phospholipid vesicles. 27 The particle size in the dispersion system can influence by the zeta potential (ZP) value. The zeta potential describes the properties of the electrostatic potential near the surface of a particle.…”
Section: Particle Size Distribution Polydispersity Index and Zeta Potentialmentioning
confidence: 99%
“…Studies have shown that the chemical stability of sensitive molecules can be improved by nanoscale particles, such as transfersomes, nanoparticles, and nanostructured lipid carriers (NLCs). [17][18][19][20] In the cosmetic and pharmaceutical industries, NLCs have received much attention for use in conserving biological properties, controlling release, and enhancing bioavailability. 21 In our preliminary study, 22 some NLC factors were screened to select their relevant ranges for encapsulation of phenolics from CFE.…”
Section: Introductionmentioning
confidence: 99%